Investigation of Summer Learning Loss in the UK—Implications for Holiday Club Provision - Shinwell, Jackie; Defeyter, Margaret Anne (Frontiers in Public Health, 2017)
This study sought to examine whether summer learning loss occurs in spelling and word reading in a population of 77 primary school aged children aged between 5-10 years (37 boys, mean age 100 months, SD 18months, and 40 girls mean age 103 months, SD 16 months) attending three schools in areas of low SES in Scotland and the North East of England. Word reading and spelling was measured using the word reading and spelling sub-tests of the Wide Ranging Achievement Test (WRAT 4). Participants were tested on three occassions: immediately before and immediately after a seven week summer break, and again after seven weeks of teaching. The results showed a significant main effect of time for spelling scores, F (2,136) = 21.60, p < .001.1, ηp 2 = .241. Post-hoc analysis (t(73) =4.84, p=<.001) showed that spelling scores were significantly higher at the end of the summer term (M=26.57) than at the start of the new academic year (M=25.38). Likewise, spelling scores after seven weeks post return to school (M= 27.61) were significantly higher than at the start of the Autumn term t(73)= 7.79, p=<.001. Performance in spelling declined when children returned to school immediately after the summer holiday (M=25.38) but seven weeks later, performance had improved beyond the baseline reported immediately before the summer break (M=26.57) (t(73)=4.40, p=<.001). There was also a main effect of school in relation to spelling scores, (F(2,68)= 6.49, p < 0.05, ηp 2 = .160), with children from school 2 and school 3 outperforming children from school 1. There was no signficant main effect of gender (F (1,68) = 1.47, p > 0.05, ηp 2 = .021 ). None of the interactions were significant. There was no main effect of time on word reading scores (F (2,136) = 1.12, p = >0.05 ηp 2 = .016 ). However there was a main effect of school (F(2,68) = 4.85, p = <0.01 ηp 2 = .005 ) in relation to reading scores, with children from school 2 and school 3 outperforming children from school 1. There was no significant main effect of gender (F (1,68)